3D hierarchical architectures of CoSe2 nanoparticles embedded in rice‐derived hard carbon for advanced sodium storage. Issue 3 (2nd September 2022) - Lin, Congjian; Zhang, Jintao; Lim, Yew Von; Yan, Dong; Li, Ke; Leong, Zhi Yi; Vafakhah, Sareh; Li, Yifan; Silva, Arlindo; Yang, Hui Ying
Abstract: A low‐cost and feasible method to fabricate three‐dimensional (3D) hierarchical composites composed of CoSe2 nanoparticles embedded in rice‐derived hard carbon (HC) interconnected with carbon nanotubes (CNTs) is devised in this study. The deployment of CoSe2 in the elecrode has provided a very high rate capacity, which is crucial for sodium‐ion commercialization. The deployment of HC with CNTs further provides a 3D hierarchical structure effective in shortening the diffusion paths of both electrons and Na + ions, offering abundance of active sodium storage sites. Consequently, the CoSe2 acted as an active material with the carbonaceous template, a commonly utilized sodium‐ion battery anode material, which exhibited a superior reversible capacity of 550 mAh g −1 at 0.5 A g −1, outstanding rate performance (451 mAh g −1 at 20 A g −1 ) and excellent cycling performance (~100% capacity retention over 2500 cycles at 20 A g −1 after electrochemical stabilization). Abstract : A low‐cost and sustainable method was developed for the synthesis of three‐dimensional (3D) hierarchical composites composed of CoSe2 nanoparticles embedded in rice‐derived hard carbon interconnected with carbon nanotubes (CoSe2 @RHC@CNTs) for efficient sodium storage. Benefiting from its prominent structural and compositional features, CoSe2 @RHC@CNTs as sodium‐ion batteries anode showed enhanced sodium storage properties with high reversible capacity (550 mAh g −1 at 0.5 A g −1 ), excellent rate capability (451 mAh g −1 at 20 A g −1 ) and ultra‐long cycle life (100% capacity retention over 2500 cycles after electrochemical stabilization).